Hubungan Tingkat Pendidikan dan Pemberian ASI Ekslusif Dengan Kejadian Diare Pada Bayi di Kabupaten Bojonegoro - Zari, Afina Puspita; Ernawati, Meirina (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
In Indonesia, diarrhea still becomes a significant health problem with a high number which causesExtraordinary Events (KLB). Diarrhea cases in Bojonegoro Regency constitute as the fourth leading causeof infant death with 26.237 cases. One of the factors causing diarrhea is the mother's education level andexclusive breastfeeding. This study aims to discover whether there is a relationship between the educationlevel and exclusive breastfeeding with diarrhea incidence of infants in Tinumpuk Village, BojonegoroRegency. This research type was observational with a cross-sectional research design and a quantitativeapproach. The writer conducted interviews using an instrument questionnaire distributed door to door inevery house in Tinumpuk Village. Finally, this study indicated the mother's education level with a p-value(0.000) <0.05 and exclusive breastfeeding with a p-value of 0.038 <0.05. This result revealed therelationship between the education level and exclusive breastfeeding with the incidence of diarrhea ininfants.